Specific Metabolites Involved in Antioxidation and Mitochondrial Function Are Correlated With Frailty in Elderly Men - Meng, Li; Shi, Hong; Wang, Da-guang; Shi, Jing; Wu, Wen-bin; Dang, Ya-min; Fan, Guo-qing; Shen, Ji; Yu, Pu-lin; Dong, Jun; Yang, Rui-yue; Xi, Huan (Frontiers in Medicine, 2022)
Background: As as an age-related syndrome, frailty may play a central role in poor health among older adults. Sarcopenia overlaps with the physical domain of frailty, Perturbations in metabolism may play an important role in frailty or sarcopenia;however, the metabolites associated with frailty, especially overlapping with sarcopenia remain unclear. In this study, we aimed to explore whether amino acids and lipid-related metabolism are correlated with frailty, especially overlapping with sarcopenia , to gain insight into potential biomarkers and possible biological mechanisms and to facilitate their management.. Methods: We applied a targeted high-performance liquid chromatography-tandem mass spectrometry approach in serum samples from 246 Chinese older men (age 79.2±7.8 years) with frailty (n=150), nonfrailty (n=96), frailty and sarcopenia (n=52), nonfrail and nonsarcopenic control (n=85). Frailty was evaluated using Freid phenotype criteria, sarcopenia was defined by diagnostic algorithm of Asian Working Group on Sarcopenia. A panel of 29 metabolomic profiles was assayed and included different classes of amino acids, carnitines, acylcarnitines, and lysophosphatidylcholines. Multivariate logistic regression was used to screen the metabolic factors contributing to frailty, and orthogonal partial least squares discriminant analysis was used to explore important factors and distinguish different groups. Results: In older men demonstrating the frail phenotype, amino acid perturbations included lower tryptophan and higher glycine levels. With regard to lipid metabolism, the frailty phenotype was characterized by lower concentrations of isovalerylcarnitine (C5), LPC16:0 and LPC18:2, while higher levels of octanoyl-L-carnitine (C8), decanoyl-L-carnitine (C10), dodecanoyl-L-carnitine (C12) and tetradecanoyl-L-carnitine (C14). After adjusting for several clinical confounders, tryptophan, LPC18:2, LPC 16:0 and C5 were negatively correlated with frailty, and C8 and C12 were positively related to frailty. We preliminarily identified metabolic profiles that may distinguish older men with frailty from those without frailty. Importantly, a set of serum amino acids and LPCs (LPC16:0, LPC18:2, and tryptophan) was characterized in older adults with an overlap of frailty and sarcopenia. The metabolites that were most discriminating involved in antioxidation and mitochondrial dysfunction. Conclusions: These present metabolic analyses may provide valuable information on the potential biomarkers and possible biological mechanisms of frailty. The findings obtained may offer insight into their management in older adults.